Military Occupation and Human Rights Protection - Klaudia Hraníková (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The aim of the paper is to generally outline the relationship between the law of armed conflict and human rights protection, and thus the usability of the human rights standards in the military occupation. The paper provides an analysis of the application of relevant legislation and will aim to explore complementarity, compatibility and possible exceptions to the applicability of those standards. Finally, the paper aims to identify practical and legal loopholes in the implementation of the human rights commitments and options for addressing these international legal problems.